A sneeze: an unusual trigger for aortic dissection. (3rd December 2013) - Upadhyaya, Subramanya G N; Large, A
Abstract : We describe a rare case of type B thoracic aortic dissection resulting from a forceful sneeze in a 57-year-old man. The presenting clinical features were not typical and consisted of pleuritic chest pain and breathlessness following a forceful sneeze. There was no haemodynamic compromise. The diagnosis was made incidentally when he underwent a CT pulmonary angiography as part of pulmonary embolism work-up.